PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - ARSYA, TANISA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This study aims to analyze the influence of organizational culture and organizational commitment to employee performance NAV Jaya Mandiri Surabaya. The population in the study were all employees of PT NAV JAYA Jaya Mandiri Surabaya Pusat, NAV Soetomo, NAV Walikota Mustajab, and NAV Billiton. The samples in this study were taken by using purposive sampling method and sample size was 33 employees. The analysis technique used in this study is the technique of multiple linear regression analysis.Based on the research that has been done can be seen that organizational culture has a significant influence on employee performance PT NAV Jaya Mandiri Surabaya . Organizational commitment has a significant influence on employee performance PT NAV Jaya Mandiri Surabaya . Factors organizational culture and organizational commitment has influence simultaneously or jointly to employee performance PT NAV Jaya Mandiri Surabaya. Keywords: organizational culture, organizational commitment and employee performance.